Anti-doping research and the Helsinki Declaration: (mis)match?. (18th May 2020) - Sanchini, Virginia; Devriendt, Thijs; Borry, Pascal
ABSTRACT: The fight against doping in sport is internationally coordinated by the World Anti-Doping Agency (WADA). Through its World Anti-Doping Code, WADA aims to harmonize anti-doping policies, rules and regulations. One key reference document bound to the Code is the International Standard for Laboratories (ISL), which mainly specifies the criteria that must be met for laboratory accreditation, as well as standards to adopt for the production of valid test results and evidentiary data. Within the ISL, the Code of Ethics refers to the Helsinki Declaration as a guiding framework for anti-doping research. However, inasmuch as anti-doping research structurally differs from human subject research as considered by the Helsinki Declaration, the applicability of the latter to anti-doping research can be called into question. In this work, we discuss how key principles of the Helsinki Declaration apply to anti-doping research and highlight frictions, incompatibilities and misalignments. Furthermore, we indicate possible solutions for operationalizing the Helsinki principles within the context of anti-doping research.